(untitled) (Research, Society and Development, 2020)
This article analyzes the life, the Human Rights and the contemporary education, based on Giorgio Agamben thought, as philosofical devices, from the human figure of the Homo sacer; it points out forms of naked life in its expressions of violence and the violations occasioned by the biopower and which leads to the thanatopolitics; it highlights the power of the education in Human Rights as an necessary reflection in the pandemic times which we are living, denoted by the death, and the politic challenge of ensuring the life with human dignity. It is a bibliographical research - Agamben (2012, 2015, 2020) and theorists whom served him as background, mainly Foucault (1987, 2002, 2013, 2014), Arendt (1989, 2001), Deleuze e Guattari (1995) and Deleuze and Parnet (1998), among others who crossed his political thought and/or essayed it, looking for the confluence with theorists that substantiate the Human Rights discussion and education, beyond of studies made during the doctoral process of the autor. The results reveal that the society of the discipline, of the control over the life, keeps in its limiar the making die as an calculus of death; the tanatopolitc that bring to the scene the existance of the Homo sacer, the naked life, the mere life; and it points out the education in Human Rights as of decolonize caracter and decolonial, as a facing way, of resitance and of construction of the human life.